Akibat Hukum dan Pertanggungjawaban Terhadap Perjanjian Elektronik Yang Dibuat Oleh Anak di Bawah Umur - Raphaellee Peters Putra Usman; Moody Rizqy Syailendra Putra (Dinasti Research, 2024)
Difficulty determining the correct identity on the internet thus affecting the validity of the contract. Therefore, it is known that payment failures are likely to occur in online sales and e-commerce transactions. In online sales and electronic commerce transactions, it cannot be known for certain whether the parties involved have the legal skills as intended in Article 1320 of the Civil Code. Using the approach used in this research is a legal approach, a conceptual approach. The statutory approach method requires an understanding of legal and regulatory hierarchies and principles. The conceptual approach exists as long as it does not deviate from existing legal regulations. The research results show that the legal consequences of transactions by minors in e-commerce that clearly do not fulfill one of the subjective requirements above are the weak legal force of the contract. A contract entered into by an incompetent person can be canceled based on the wishes of the other party who feels disadvantaged. This is due to the validity of electronic contracts involving minors as one or both parties have violated the provisions of the validity of the agreement according to law. However, the contract will remain in effect and the parties remain bound to fulfill it as long as no one objects to one of the legal terms of the agreement not being fulfilled. Parents must be good role models, one word and one action, fair and not discriminate between children in terms of age, gender, strengths or weaknesses and respect children's potential with an attitude of love and affection.